Language Using of Code-Mixing in Captions and Comments on Instagram Content Creators' - Sakina, Silfi Aliya; Sigit Haryanto (LPPM Universitas Advent Indonesia, 2026)
Digital communication has increased the use of code-mixing among social media users, such as on Instagram. This research examines Indonesian-English code-mixing found in both captions and comments of three popular Indonesian bilingual content creators. Using a descriptive qualitative approach, 50 instances of code-mixing were identified and analyzed over a 4-month observation period. Each instance was thoroughly examined and categorized according to Muysken’s (2000) typology, which includes insertion, alternation, and congruent lexicalization. In addition, the underlying motivations for code-mixing were analyzed using Holmes’ (1992) motivational framework. Results show that insertion form (40%), followed by alternation (32%) and congruent lexicalization (28%). Motivationally, prestige and affective expression were the most salient factors, indicating that English serves both as a marker of status and as a means to connect emotionally with followers. Unlike previous studies that focused only on captions or product-promotion discourse, this research combines the classification of code-mixing types (Muysken, 2000) and motivational analyses (Holmes, 1992) across both captions and comments, providing a more comprehensive understanding of bilingual interaction in digital communication.